2019
DOI: 10.1038/s41586-019-1611-7
|View full text |Cite
|
Sign up to set email alerts
|

Release from UNC93B1 reinforces the compartmentalized activation of select TLRs

Abstract: Nucleic acid-sensing Toll-like receptors (TLRs) are subject to complex regulation to facilitate recognition of microbial DNA and RNA while limiting recognition of self-nucleic acids 1 . Failure to properly regulate these TLRs can lead to autoimmune and autoinflammatory disease [2][3][4][5][6] . Intracellular localization of these receptors is thought to be critical for self vs. non-self discrimination 7 , yet the molecular mechanisms that reinforce compartmentalized activation of intracellular TLRs remain poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 28 publications
2
65
1
Order By: Relevance
“…66 The release of TLR9 from the ER is controlled by several mechanisms including tyrosine-based motifs in TLR9 cytoplasmic tail, [67][68][69][70] and phosphorylation of TLR9. 71 Key proteins required for TLR9 traffic from ER to endosomal compartments include glycoprotein 96 (gp96), 72 UNC93B1, 73,74 adapter protein 3 (AP-3), 75,76 a protein associated with TLR4 (PRAT4A), 77 and Slc15a4. 75 The unique localization and trafficking requirements of the nucleic acid-sensing TLRs 7-9 serve as a regulatory mechanism to limit immune responses to host nucleic acids; and indeed, artificial localization of TLR9 to cell surface causes autoimmune manifestations.…”
Section: Tlr9 Overview: Type and Distribution Structure And Ligandsmentioning
confidence: 99%
“…66 The release of TLR9 from the ER is controlled by several mechanisms including tyrosine-based motifs in TLR9 cytoplasmic tail, [67][68][69][70] and phosphorylation of TLR9. 71 Key proteins required for TLR9 traffic from ER to endosomal compartments include glycoprotein 96 (gp96), 72 UNC93B1, 73,74 adapter protein 3 (AP-3), 75,76 a protein associated with TLR4 (PRAT4A), 77 and Slc15a4. 75 The unique localization and trafficking requirements of the nucleic acid-sensing TLRs 7-9 serve as a regulatory mechanism to limit immune responses to host nucleic acids; and indeed, artificial localization of TLR9 to cell surface causes autoimmune manifestations.…”
Section: Tlr9 Overview: Type and Distribution Structure And Ligandsmentioning
confidence: 99%
“…It has been reported that a chaperone protein, UNC93B1, regulates the stability and/or transportation of these TLRs. Furthermore, TLR researchers have investigated whether UNC93B1 is related to the regulation of TLR functions Majer, Liu, Woo et al, 2019). As TLR7, TLR8 and TLR9 share some common features in sequence homology, function and structure, they constitute the TLR7 subfamily and harbor 26 LRRs, thus being the longest members of the TLR family, sense singlestranded nucleic acids and have a characteristic insertion between LRR14 and LRR15 called the Z-loop (Tanji et al, 2013;Ohto et al, 2015;Zhang et al, 2016;Fig.…”
Section: General Features Of Tlr8mentioning
confidence: 99%
“…The human UNC93B1 consists of 597 amino acids and is a 12 transmembrane domain containing protein located in endosomal membranes [31]. It acts as a trafficking chaperone of the intracellular nucleic acid-sensing Toll-like receptors (TLRs) 3, 7 and 9 [32][33][34][35]. These TLRs are essential components of the innate immune system and activated when pathogen derived nucleic acids appear in endolysosomes.…”
Section: Discussionmentioning
confidence: 99%